2014
DOI: 10.1093/emph/eou002
|View full text |Cite
|
Sign up to set email alerts
|

Interbirth intervals: Intrafamilial, intragenomic and intrasomatic conflict

Abstract: A longer time between births increases child survival. Night-waking to suckle may benefit infants by delaying a mother's return to fertility. Cells of fetal origin colonize the mother's body during pregnancy and persist until subsequent pregnancies. These cells will have been selected to extend inter-birth intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 36 publications
1
37
0
Order By: Relevance
“…The phenotype of infants with PWS fits evolutionary models in which PEGs have been selected to enhance suckling and night waking because of a benefit to infant fitness at a cost to maternal fitness [5,6,7,8]. While our paper has focused on feeding behaviors, the phenotype of older children with PWS promises to provide similar insight into kin-mediated tradeoffs in the evolution of other distinctive aspects of human childhood.…”
Section: Future Directionsmentioning
confidence: 71%
See 3 more Smart Citations
“…The phenotype of infants with PWS fits evolutionary models in which PEGs have been selected to enhance suckling and night waking because of a benefit to infant fitness at a cost to maternal fitness [5,6,7,8]. While our paper has focused on feeding behaviors, the phenotype of older children with PWS promises to provide similar insight into kin-mediated tradeoffs in the evolution of other distinctive aspects of human childhood.…”
Section: Future Directionsmentioning
confidence: 71%
“…Haig and Wharton suggested that PEGs from the PWS region had evolved to promote suckling during early infancy and to resist introduction of alternative foods at the time of weaning [5]. The major benefit for infants was conjectured to have been longer delays until births of younger sibs caused by prolongation of their mothers' lactational amenorrhea [8]. Conception is followed by birth nine months later.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If a woman acquires a new mate he will have no genetic interest in her previous children, a condition that is associated with infanticide in many species [51], and with higher rates of child homicide, at least in Western countries [52]. This motivation may lead to a woman's new partner preferring a shorter IBI than a woman would [53,54]. This conflict of interest between reproductive partners means that a father may want a woman to devote more of her reproductive resources towards a current child that the father knows is his, rather than to her future offspring whom he may or may not father.…”
Section: (I) Women Sequentially Acquire New Matesmentioning
confidence: 99%